UPAYA ORANGTUA MENDIDIK ANAK MENCINTAI ALQURAN - Zulhammi Chaniago (Institut Agama Islam Negeri Padangsidimpuan, 2020)
Rasulullah Saw has left the Alquran to his people as the greatest miracle that is unmatched and will be awake until the Day of Resurrection. Parents are obliged to educate their children to love the Alquran because the Alquran is a life guide for Muslims.Parents' methods of educating children include listening to Alquran readings to children, exemplary, family tadarus, story method, strengthening motivation to memorize the Alquran, pray for children to love the Alquran, and finding a good environment for children